Analisis Flow Experience Pemustaka Pada Website Repositori Universitas Sriwijaya - Rts. Tiara Hilda Safitri; Beta Ria Febrianti; Murzilawati Murzilawati (Tik Ilmeu : Jurnal Ilmu Perpustakaan dan Informasi, 2023)
This research is motivated by information technology advances that force users to use repositories as a source of information. The capabilities and challenges users face in using the repository website can be a benchmark for achieving a flow experience. Objectives: To determine the level of flow experience, the factors that influence the flow experience, and the most dominant factors affecting users' flow experience. Input and considerations in making website development decisions and achieving excellent service. The research method used is quantitative research and exploratory factor analysis. The sample is 106 using purposive sampling. The result is that most users who use the UNSRI repository are women, 64.49%, aged 16-25 years, 88.79% with the latest educational background, the majority being senior high school students, amounting to 63.55%. The assumption is that the users using the UNSRI repository are students pursuing undergraduate education. The level of users' flow experience on the UNSRI repository website, as many as 57 users, is categorized as flow. Then there are 33 users classified as frustrated. Libraries can review procedures for accessing files stored in the repository. Training or information literacy on using repository files should be carried out regularly